Proteomic tools for the characterization of cell death mechanisms in drug discovery. Issue 7 (3rd May 2015) - Anania, Veronica G.; Lill, Jennie R.; Cutler, Paul; Voshol, Hans
<x xml:space="preserve">Abstract</x> This review focuses on the use of proteomic tools for the characterization of cell death mechanisms that have contributed to drug discovery efforts. Resistance to cell death plays a major role in the development of many diseases, including numerous types of malignancies. Using a multitude of proteomic approaches, including protein–protein interaction studies, phosphorylation site mapping, ubiquitination site identification, and differential quantitative approaches, various cellular death pathways such as apoptosis and necroptosis have been investigated. These studies have aided in the development of therapeutic strategies or allowed dissection of clinical results to evaluate the success of clinical trials in addition to contributing to our understanding of these biological pathways. Here, we address the new wave of discoveries enabled by advancements in mass spectrometric technology and bioinformatic infrastructure that will hopefully lead to clinically efficacious strategies to overcome resistance to apoptosis and therefore offer improved treatment options for patients.